Biological control of the false root-knot nematode Nacobbus aberrans by Pseudomonas protegens under controlled conditions - Lax, Paola (2013)
The use of antagonistic biological agents, such as fungi and bacteria, offers an economical and safe strategy to manage planteparasitic nematodes in infested fields. The false root-knot nematode, Nacobbus aberrans, is a damaging parasite of many agronomic and horticultural crops in South and North America. The management of this nematode is challenging and often not profitable for farmers. In greenhouse tests, conducted in Argentina, applications of the strain Pseudomonas protegens CHA0 and its isogenic derivative ARQ1 (used as control) at a rate of 108 cfu ml1 suppressed infection and reproduction of N. aberrans on tomato roots. However, neither of the strains promoted plant root or shoot growth of the treated plants. Root colonization by the bacteria was assessed by specific PCR-RFLP protocols and fluorescence microscopy. The results obtained in this preliminary study were encouraging and showed the potential of P. protegens CHA0 to be used for the management of the false root-knot nematode on tomato.